THE EFFECT OF BRAND IMAGE AND TRUST ON FRESHMEN’S DECISION MAKING - Muhammad Husin Nur Muzakki; Septylyta Rahmita Putri (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2022)
This study to examine the effect of brand image, trust, and Instagram social media on new student decision making in determining higher education levels.. This study involved 210 new students of Kusuma Husada University Surakarta as subjects in the study. This study uses a Structural Equation Modeling (SEM) approach with AMOS Software as a data analysis and testing tool. The measurement or testing is carried out using four stages of testing, namely using the t test or partial testing of brand image, trust, in decision making with the results of the Sig value below (0.05). This study confirms brand image, and trust was found to have a significant effect on Instagram social media, and finally Instagram social media was found to mediate the influence of brand image and trust on the decision making of new students at Kusuma Husada University Surakarta. This study can be used as a reference by marketing management practitioners in designing alternative strategies to improve brand image and consumer confidence and increase consumer confidence in making decisions in choosing a product or service.